2023
DOI: 10.1007/s43494-023-00088-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Procedures and Outcomes of Choice-Based Interventions with Children

Abstract: In behavior-analytic clinical work and research, opportunities for choice can be arranged as an independent variable, and response allocation among choice options can be measured as a dependent variable (i.e., engaging in one response given two or more concurrently available options). Choice-based interventions provide behavior analysts with tools to promote their clients’ rights to autonomy and self-determination by incorporating client preference. The purpose of the current article is to systematically revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…In these cases, clinicians should generally implement the highest preferred treatment if that intervention can be implemented with high fidelity. Additional research is needed to determine the effect that choice-based interventions have on durable behavior change when fidelity errors occur (Kestner et al, 2023). Notably, in Frank-Crawford et al (2019), one participant showed preference for the least efficient intervention.…”
Section: Ethical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, clinicians should generally implement the highest preferred treatment if that intervention can be implemented with high fidelity. Additional research is needed to determine the effect that choice-based interventions have on durable behavior change when fidelity errors occur (Kestner et al, 2023). Notably, in Frank-Crawford et al (2019), one participant showed preference for the least efficient intervention.…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…This is reflected in the Behavior Analyst Certification Board (BACB) Ethics Code, which states that behavior analysts should consider relevant factors such as client and stakeholder preference when implementing behavior‐change procedures (BACB, 2022). Evaluating choice is one way to obtain information about preference (Kestner et al, 2023). An early evaluation of objective choice for token economy arrangements was reported by Iwata and Bailey (1974); however, that approach remained uncommon for decades.…”
mentioning
confidence: 99%